Sport for Development and COVID-19: Responding to Change and Participant Needs - Dixon, Marlene A.; Hardie, Ashlyn; Warner, Stacy M.; Owiro, Emmaculate Awour; Orek, Dennis (Frontiers in Sports and Active Living, 2020)
As COVID-19 hit in the Spring of 2020, substantial challenges began to emerge for individuals around the world. In this empirical piece examine the impacts of COVID-19 in the sport for development (SFD) context, as it relates to the individual participant, as well as how those individual needs impact the organization itself. This case study, explores a hybrid SFD organization, Highway of Hope (HOH) in Kenya, and the actions of local leadership in response to emergent participant needs during the onset of the pandemic. Using a case study approach, involving journal responses from program youth participants and local program leadership, along with other field and meeting notes, themes were generated to highlight the most salient challenges and experiences faced by individual participants, as well as the means of addressing those challenges by HOH. Participant journals consisted of both positive and negative thematic findings. Positive experiences included Family Time, Rest, and Practicing Better Hygiene, while negative experiences revolved around Restriction of Activity, and Difficulty at Home. The overall impact on participant lives were expressed in themes such as Socio-emotional, Physical, and Sport-Specific. Further, practical implications for grassroots and hybrid SFD programs during times of unprecedented challenge and notable turning points are highlighted.